The 'Survivorship Passport' for childhood cancer survivors. (October 2018) - Haupt, Riccardo; Essiaf, Samira; Dellacasa, Chiara; Ronckers, Cecile M.; Caruso, Silvia; Sugden, Elaine; Zadravec Zaletel, Lorna; Muraca, Monica; Morsellino, Vera; Kienesberger, Anita; Blondeel, Anne; Saraceno, Davide; et al.
Abstract: Background: Currently, there are between 300, 000 and 500, 000 childhood cancer survivors (CCSs) in Europe. A significant proportion is at high risk, and at least 60% of them develop adverse health-related outcomes that can appear several years after treatment completion. Many survivors are unaware of their personal risk, and there seems to be a general lack of information among healthcare providers about pathophysiology and natural history of treatment-related complications. This can generate incorrect or delayed diagnosis and treatments. Method: The Survivorship Passport (SurPass) consists of electronic documents, which summarise the clinical history of the childhood or adolescent cancer survivor. It was developed by paediatric oncologists of the PanCare and SIOPE networks and IT experts of Cineca, together with parents, patients, and survivors' organisations within the European Union–funded European Network for Cancer research in Children and Adolescents. It consists of a template of a web-based, simply written document, translatable in all European languages, to be given to each CCS. The SurPass provides a summary of each survivor's clinical history, with detailed information about the original cancer and of treatments received, together with personalised follow-up and screening recommendations based on guidelines published by the International Guidelines Harmonization Group and PanCareSurFup. Results: The SurPass data schema contains a maximum of 168 variables and uses internationally approved nomenclature, except for radiotherapy fields, where a new classification was defined by radiotherapy experts. The survivor-specific screening recommendations are mainly based on treatment received and are automatically suggested, thanks to built-in algorithms. These may be adapted and further individualised by the treating physician in case of special disease and survivor circumstances. The SurPass was tested at the Istituto Giannina Gaslini, Italy, and received positive feedback. It is now being integrated at the institutional, regional and national level. Conclusions: The SurPass is potentially an essential tool for improved and more harmonised follow-up of CCS. It also has the potential to be a useful tool for empowering CCSs to be responsible for their own well-being and preventing adverse events whenever possible. With sufficient commitment on the European level, this solution should increase the capacity to respond more effectively to the needs of European CCS. Highlights: Treatment summary and follow-up recommendations are available to CCSs via SurPass. SurPass provides a homogeneous follow-up and screening for all European CCSs. SurPass is a solution to organise long-term follow-up care in a consistent and cost-effective way. The SurPass has the potential to be a useful tool for empowering CCSs.